Kajian Filsafiah dan Ilmiah Bimbingan Spiritual untuk Mengembangkan Welas Asih Mahasiswa Broken Home - Siddik, Riesa; Novianti, Williya; Suherman, Maya Masyita; Pahlevi, Reza (Indonesian Journal of Educational Counseling, 2024)
This article contains a study of spiritual guidance to develop compassion in Broken Home students. Having an incomplete family makes some children become victims so they have bad experiences and cause problems both physically and psychologically, such as blaming themselves, trauma, blaming their parents, etc. The highest cognitive experience that has a major impact on individual psychology is meaning. Through meaning (spirituality), individuals find and believe in their life purpose, which has an impact on the way they live their lives, including the way they solve problems. Spiritual experiences can help individuals understand problems and make the best decisions to solve them, related to transcendent experiences and related to awareness of sacred and eternal things, thereby increasing feelings of compassion, love and affection towards oneself and others. The methodological procedure used is understanding literature from various sources. It is hoped that the results of this paper will contribute to research and development of spiritual guidance models to develop students' compassion.